A bar too high? On the use of practical wisdom in business ethics. (17th June 2020) - Wolcott, Gregory
Abstract: In the business ethics literature, many argue that managerial decision making ought to be improved by more robust ethical concerns. Some see the virtue of "practical wisdom" as the key for improved managerial decision making. However, because of the epistemic limitations confronting decision makers in the face of irreducible market complexity, there is a risk that practical wisdom, employed in the context of day‐to‐day managerial decision making, becomes an impractical concept. Nevertheless, if the attempt to incorporate virtue ethics (and its related concepts) into business practices is laudable, if indeed a virtuous life is worth pursuing and practical wisdom plays an essential role toward that end, it is important to attempt to salvage practical wisdom and uncover its appropriate usage. Thus, this article pursues two major ends. First, upon surveying some of the prominent and standard usages of the term, it articulates concerns, rooted in epistemic limitations, about the way that practical wisdom appears in business ethics literature. Second, it offers a new way forward for understanding "practical wisdom." By contextualizing day‐to‐day, rule‐based managerial decision making within the ethical value of the market order, practical wisdom reappears as the higher‐order capacity to pursue vocations, as morally worthwhile projects, in business.